2017
DOI: 10.24200/sci.2017.4504
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Outer Diameter of Multi-Walled Carbon Nanotubes on Fracture Behavior of Epoxy Adhesives

Abstract: KEYWORDSMulti-walled carbon nanotubes; Toughened adhesives; Fracture energy; Cohesive zone model; Double cantilever beam.Abstract. In this paper, the in uence of the outer diameter of multi-walled carbon nanotubes (MWCNTs) on the fracture behavior of epoxy adhesives was investigated experimentally and numerically. MWCNTs with three di erent outer diameters of less than 8, 20-30, and 50-80 nm were used to toughen the epoxy adhesive. Double Cantilever Beam specimens were tested to determine the fracture energy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…By these explanations, it is concluded that the interphase plays an effective role in the percolation of nanoparticles. Figure 6 also reflects the roles of "R" and "t" parameters in the fraction of percolating network in the nanocomposites according to Equations (12) and (13) at φ f = 0.02, l = 5000 nm and A = 0.02. The smallest level of "R" and the largest value of "t" obtain the highest fraction of the network.…”
Section: Parametric Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…By these explanations, it is concluded that the interphase plays an effective role in the percolation of nanoparticles. Figure 6 also reflects the roles of "R" and "t" parameters in the fraction of percolating network in the nanocomposites according to Equations (12) and (13) at φ f = 0.02, l = 5000 nm and A = 0.02. The smallest level of "R" and the largest value of "t" obtain the highest fraction of the network.…”
Section: Parametric Analysismentioning
confidence: 99%
“…Many researchers have focused on polymer/carbon nanotubes (CNT) nanocomposites because their very low volume fractions show effective mechanical, thermal and chemical properties by preserving low density, transparency and simple processing [1][2][3][4][5][6][7][8][9][10]. The addition of CNT or graphene to polymers forms conductive nanocomposites, which has produced scientific interest in the research communities due to their potential applications in different fields, such as electronics and sensors [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The experiments show the remarkable improvement of electrical conductivity of polymers by the addition of CNT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wonderful levels of mechanical, electrical, thermal, and physical properties of carbon nanotubes (CNT) have motivated the increasing interests for the investigation of composites containing CNT as polymer/CNT nanocomposites (PCNT) . The electrical conductivity of CNT reaches to 10 6 S/m, but the polymer matrices usually show the conductivity of 10 −16 to 10 −12 S/m .…”
Section: Introductionmentioning
confidence: 99%
“…Some authors combined PLA with carbon nanotubes (CNTs) because CNTs advantageously improve the degradation rate as well as the mechanical and electrical properties of polymers (Hasanzadeh et al, 2019;Irfan et al, 2019;Khoramishad, Khakzad, & Fasihi, 2017;Kim, Zare, Garmabi, & Rhee, 2018;Pavón et al, 2019;Roy, Petrova, & Mitra, 2018;Simonovic et al, 2018;Zare & Rhee, 2017a;Zhang et al, 2018). Chen et al (2013) reported a high degradation rate in poly(Llactide)/CNTs nanocomposites, which largely depended on the CNT content.…”
Section: Introductionmentioning
confidence: 99%